Thursday

April 17, 2014

April 17, 2014

Posted by **molly** on Thursday, January 13, 2011 at 8:43pm.

- algebra -
**Ms. Sue**, Thursday, January 13, 2011 at 8:52pm-13=3(x+2)-10

-13 = 3x + 6 - 10

-13 + 4 = 3x

-9 = 3x

-3 = x

**Related Questions**

Algebra II/ Trig - Should the triangle be solved beginning with Laws of Sines or...

Algebra 2 - Which matrix represents the system of equations below? -10x-9y+13z=...

algebra - A line has slope negative five thirds. Through which two points could...

Algebra 1: 8th Grade - Simplify each expression. Write your answers using ...

math algebra - not sure about this can someone please help me solve for x using...

algebra - consider the following sets. A={13} B={10+13} C={10,3} D={2^5} E={2,5...

College Algebra - Let U = {5, 6, 7, 8, 9, 10, 11, 12, 13, 14}, A = {6, 8, 10, 12...

math(check answers please) - for questions 1-3,find the sum. 1.5 9/13 + 5 9/13= ...

Math - 3^2*3^3=3^5 7*0.1=7/10 5^2*5^3=5^5 3*0.1=3/10 13^2*13^3=13^5 4*0.1=4/10 ...

algebra - solve and check.label ant contradictions or identities. 5(t+1)+8=3(t-2...